KAMSO – ett hälsoekonomiskt kalkylverktyg när evidens saknas - Löfgren, Curt; Hjelte, Jan; Ivarsson, Anneli; Lohr, Wolfgang; Lundahl, Lisbeth; Sahlén, Klas-Göran; Pulkki-Brännström, Anni-Maria (Socialmedicinsk tidskrift, 2025)
In much of the public sector, the prioritisation of interventions is hindered by a lack of research on their cost effectiveness. Yet, prioritisation decisions must be made. How can the evidence base be improved in this context? This article presents a tool for assessing the cost-effectiveness of such interventions for children and young people — KAMSO. The method and a hypothetical example are presented. Cost-effectiveness is assessed from a societal perspective, using capability-adjusted life years gained as the outcome measure, and complemented by budget impacts across different parts of the public sector. Finally, the article concludes with a discussion on the future development of KAMSO.